THE EFFECT OF SMALL GROUP DISCUSSION TEACHING METHOD TO THE READING COMPREHENSION OF GRADE EIGHT STUDENTS OF SMP NEGERI 4 PEMATANG SIANTAR ON A DESCRIPTIVE TEXT - Widya Ambarita; Sanggam Siahaan; Bloner Sinurat (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The purpose of this study is to find out whether the effect of small group discussion teaching method to the reading comprehension of grade eight students of SMP Negeri 4 Pematang Siantar. This research uses quantitative research with a quasi-experimental research methodology. Creswell (2012:27),explains that "quasi-experimental includes giving tasks, but not assigning participants to groups". This research used quantitative research quasi-experimental method. The data from this study where collected and obtained through tests. The sample this research the VIII -6 as the experimental class and the VIII-9 as the control class .the test was carried out with pre-test and post-test to students using small group discussion teaching method.The research data and result findings of calculation, the research found the mean score in experimental class from pre-test to post-test are 70.40 and 82.40. than score in control class from pre-test and post-test are 70.53 and 76.73. the statistical hypothesis testing findings sample t-test are indicated ,at a level of significance of 5% (=0,05), that the t -test was 3,04 whereas t-table was 1.671 , or t-test> t-table .it can be concluded that the value of t-test was higher than the value of t-table .therefore, the alternative hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected .so, its mean that there is a significant effect of use small group discussion teaching method to the reading comprehension of grade eight students of SMP Negeri 4 Pematang Siantar